2000
DOI: 10.1007/s004670000433
|View full text |Cite
|
Sign up to set email alerts
|

Clinical presentation and natural course of idiopathic hypercalciuria in children

Abstract: Idiopathic hypercalciuria (IHC) has been reported mainly in children with hematuria in the 1980s and early 1990s, when renal sonography was just becoming routine. The presence of microcalculi, i.e., of hyperechogenic spots < 3 mm in diameter in renal calyces, was not taken into account in those studies. We attempted to outline clinical presentation and natural course of IHC not only in children with hematuria, but also in those with dysuria and/or recurrent abdominal/flank pain and a family history of nephroli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
50
2
7

Year Published

2003
2003
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(61 citation statements)
references
References 12 publications
2
50
2
7
Order By: Relevance
“…In pediatric patients with nephrolithiasis, 73% had a family history of kidney stones in at least one first-order or second-order relative, as opposed to a prevalence of 22% in a control population of pediatric renal and urologic patients (18). Of the patients with hypercalciuria, the prevalence of nephrolithiasis in the family history was 69% (18).…”
mentioning
confidence: 96%
“…In pediatric patients with nephrolithiasis, 73% had a family history of kidney stones in at least one first-order or second-order relative, as opposed to a prevalence of 22% in a control population of pediatric renal and urologic patients (18). Of the patients with hypercalciuria, the prevalence of nephrolithiasis in the family history was 69% (18).…”
mentioning
confidence: 96%
“…1,3,4 However, according to a study done by Safaei et al in Rasht, Iran, the prevalence of idiopathic hypercalciuria in males and females was the same. 5 Kalia et al reported a 10-week-old infant with hypercalciuria, 6 whereas the youngest baby in our study was 39 days old.…”
Section: Discussionmentioning
confidence: 96%
“…1 Hypercalciuria in children can lead to tubulointerstitial damage resulting in chronic kidney disease. We studied the clinical profile and benefit of therapy for children with hypercalciuria from a southern region in India.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hypercalciuria may be associated with hypophosphatemia due to mutations in phosphorus /sodium cotransporter proteins, encoded by the NPT2a gene [23][24][25] . In children with hypercalciuria, the prevalence of renal lithiasis in the family ranges from 46 to 49% [26][27][28] .…”
Section: Discussionmentioning
confidence: 99%